Balancing Financial and Socioemotional Wealth: How Zakat Empowerment Programs Influence Family Business Decisions - Gunawan Baharuddin; Bayu Taufik Possumah; Asmak Ab Rahman; Hafizah Abdul Rahim; Hareth Zuhair Alshamayleh (Jurnal Economia, 2026)
This study investigates the relationship between zakat empowerment programs and the balance of financial and socioemotional wealth (SEW) in family-owned businesses. Using survey data from 178 Muslim-owned family businesses across three countries, this study examines how strategic zakat distribution influences business decision-making and performance. Study findings reveal that businesses with formalized zakat empowerment programs demonstrate higher levels of SEW preservation while maintaining comparable financial performance to those with traditional zakat practices. Path analysis indicates that strategic zakat distribution positively mediates the relationship between family values and business sustainability. Furthermore, cluster analysis identifies three distinct approaches to balancing financial and socioemotional wealth through zakat: community-focused, business-integrated, and tradition-oriented. This study contributes to SEW theory and Islamic business ethics by offering empirical evidence on how religious financial obligations can be strategically leveraged to support both socioemotional and financial goals in family firms.